CERITA BERGAMBAR BIOGRAFI KAREL FREDERIK HOLLE "SANG BUDAYAWAN DI PRIANGAN TIMUR" - Winny Mardiani, - (2018)
Sejarahmerupakansalahsatuhal yang perludiketahuiolehsemua orang, baik yang mudasampaitua.Kiprahseorangsejarawanharuslah di edukasikankepadakhalayakumum.Semakinberkembangnyazaman, sedikit demi sedikitsejarahataukiprahseorangsejarawanterlupakankarenaterlalusibukdenganarusteknologi di zamansekarang, dansejarahdianggapmembosankanolehsebagian orang.Kiprahsejarawan di Indonesia, khususnya di daerahPrianganTimur, Garutpantasmendapatkantempat yang sesuai. Salah satunyaialahdengancaramendokumentasikandanmemperkenalkannyakekhalayakramai, khususnyaanak-anak, agar kitasebagaipenerusbangsatidaklupaterhadapsejarahsendiri. Permasalahantersebutmenjadi ide yang dikembangkanmenjadigagasanpenciptaandenganperumusanmasalah: bagaimanamengembangkan ide "biografitokoh" danmemvisualisasikannyadalamceritabergambarKarelFrederikHolle "Sang Budayawan di PrianganTimur". Metode yang digunakandalampenciptaaninimeliputi ide berkarya, tahappendekatan, observasi, klasifikasipembaca, pengolahan ide, proses berkarya. Dalampembuatancergaminipenulismenggunakanteknikgabunganyaitu manual dan digital, tahap-tahapannyaadalah: Pembuatandesaintokoh, synopsis, storyline, storyboard, sketsaawal, pewarnaan manual, penintaan, dan edit digital. Edit digital melalui proses scanning, penyesuaianwarna digital, lettering, pembuatancover, pencetakan, danpenjilidan. Hasildaripenciptaaniniadalahsebuahbukuceritabergambarbiografi yang dibuatuntuanakusia 10-12 tahun. Berukuran 21x21 cm yang terdiridari 86 halamandengankertasartpapper, danjilidhardcover. Menggunakan genre realistic stories, bentukarakter semi realis, danmenggunakanpilihanwarna-warna pastel.Cergaminidiharapkandapatbermanfaatbagisemua orang khususnyaanak-anakuntuklebihmengetahuilagimengenaitokohsejarawan yang sudahberjasapadawaktunya.Penulismerekomendasikanuntukpenelitiselanjutnya, buatlahceritabergambarmengenaitokoh-tokohpenting yang berjasa di Indonesia yang hampirterlupakanuntukmengenalkankembalikepadasemua orang, lalubuatlahcerita yang targetnyalebihmenyeluruhkesemuausia. Penulisjugaberharapkaryainidapatmenginspirasipara illustrator, sertamenjadibahankajianpembelajaran yang berhubungandenganilustrasidandesainbagiduniapendidikansenirupa;---History is one thing that needs to be known by everyone, both young and old. The work of a historian must be educated to the general public. The growing age, little by little history or the progress of a historian is forgotten because it is too busy with the current technology, and history is considered boring by some people. The progress of historians in Indonesia, especially in the East Priangan area, Garut deserves a suitable place. One of them is by documenting and introducing it to the public, especially children, so that we as the nation's successors will not forget our own history. The problem becomes an idea developed into the idea of creation with the formulation of the problem: how to develop the idea of "character biography" and visualize it in the story depicting KarelFrederikHolle "The Cultural in Eastern Priangan". The method used in this creation includes ideas of work, stage of approach, observation, classification of readers, processing of ideas, process of work. In making this comic, the writer uses a combination of manual and digital techniques, the stages are: Making character designs, synopsis, storylines, storyboards, initial sketches, manual coloring, requests, and digital editing. Digital editing through the scanning process, digital color adjustments, lettering, making covers, printing, and binding. The result of this creation is a biographical storybook made for children aged 10-12 years. 21x21 cm in size consisting of 86 pages with artpapper paper, and hardcover volume. Using realistic stories, semi-realist characters, and using a selection of pastel colors. This book is expected to be useful for all people, especially children, to know more about the figures of historians who have contributed in time. The author recommends for the next researcher, create a pictorial story about important figures who have contributed to Indonesia who are almost forgotten to reintroduce to everyone, then make a story that targets more thoroughly to all ages. The author also hopes that this work can inspire illustrators, as well as being a learning study material related to illustration and design for the world of art education.